A cyclic (intermittent) drying schedule for Macassar ebony-the prevention of collapse deformation and the utilization of mechano-sorptive creep gradient - Li, Jing; Zhang, Jingyuan; Wang, Bingquan; Ren, Shixue; Zhan, Jian-feng (Drying technology, 2024)
Ebony wood is often defective, showing severe cracks and deformations during manufacturing processes, and requires ample times for drying. The continuous drying has been proved to result in enormous collapses during the entire drying stage. In order to control the extent of collapses and further prevent these defects, a low temperature pre-freezing procedure was projected and followed by a cyclic drying program. This cyclic (intermittent) drying schedule was proposed based upon a so-called "mechano-sorptive creep gradient" (MSCG) strategy and elaborated by a "corresponding temperature differentia" (CTD) concept. The MSCG and CTD variables provided the theoretical explanation and the operational instruction to the cyclic drying test, respectively. The overall evolutions of collapse and transversal shrinkage of the ebony lumber boards were quantitatively investigated during the entire period of a cyclic drying process. Furthermore, the relationships between collapse and moisture content as well as cross section orientation were determined quantitatively. Under this specified pre-freezing plus cyclic drying method, the averaged collapse deformations were significantly decreased, with the maximum collapse variables accounting for 20 ∼ 30% of those under continuous cases, fully achieving the collapse controlling objective.